1991
DOI: 10.1149/1.2085415
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Mechanisms at the n ‐ FeS2 /  I  Interface: An Electrolyte Electroreflectance Study

Abstract: Monocrystalline normaln‐FeS2 (pyrite) in contact with the I−/In− redox couple was studied by electrolyte electroreflectance (EER) and conventional electro‐ and photoelectrochemical techniques. The EER signal originating from the 3.13 normaleVS:normalp→normalFe:enormalg , direct transition in pyrite can be used to determine precisely its flatband potential false(VFBfalse) , even in the presence of a high concentration of bandgap surface states, which is typical for this semiconducting transition metal sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 7 publications
2
6
0
Order By: Relevance
“…The overall behavior suggests that sulfur deposition neutralizes the charge in intrinsic surface states on pyrite, relaxing the upward bent bands and thereby decreasing the photocurrent.With sufficient neutralization of the charge in surface states, an apparent positive shift of about i 1 V occurs in the flat band potential. This is the same behavior observed by others for several i different redox couples(11)(12)(13)(14)(15). It should be noted that the photocurrent does not go entirely to zero with sulfur deposition; thus, the actual flat band potential is not determined.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…The overall behavior suggests that sulfur deposition neutralizes the charge in intrinsic surface states on pyrite, relaxing the upward bent bands and thereby decreasing the photocurrent.With sufficient neutralization of the charge in surface states, an apparent positive shift of about i 1 V occurs in the flat band potential. This is the same behavior observed by others for several i different redox couples(11)(12)(13)(14)(15). It should be noted that the photocurrent does not go entirely to zero with sulfur deposition; thus, the actual flat band potential is not determined.…”
supporting
confidence: 86%
“…7) represents the oxidation of HS to S, and the cathodic peak at -0.61 the reverse process (16). At potentials between -0.76 and -0.16 V on the positive potential sweep, the photocurrent is similar to the behavior observed in the absence of hydrosulfide, i.e., zero photocurrent induced by cathodic dissolution of pyrite at -0.76 V and a gradual increase in photocurrent with increasing potential; however, sulfur deposition causes a sudden decrease in the photocurrent at potentials greater than -0.06 V. The decrease may be associated with either a decrease in band bending at the surface (i.e., an apparent shift in the flat band potential to more positive potentials, similar to the model proposed in references (11,12)), or to the formation of a passivating sulfur layer at the surface, which inhibits charge transfer. The decrease in current on the voltammetry curve with sulfur deposition indicates a passivated surface.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Furthermore, it has been previous suggested that the I − /I 2 redox couple could facilitate electron transfer through a direct ligand field interaction with the surface, which could reduce recombination at the semiconductor/electrolyte interface. 23,65,66 The favorable interaction of I − /I 2 redox couple with the surface may also be supported by the outstanding stability of iron pyrite PEC cells and high electrocatalytic activity of pyrite compounds for the iodine/iodide reaction. 28,65−68 In such a case, inner-sphere electron transfer explains the observed larger photocurrents.…”
Section: ■ Resultsmentioning
confidence: 99%
“…In addition, several An intrinsic surface state is also consistent with studies of the photoelectrochemical behavior of pyrite with the redox couples V 2+ N 3+ , Fe2+lFe3+, Br'/Br2, and C17CI2. Jaegermann and Tributsch [1983] and Salvador et al [1991 J studied the anodic photocurrents for these redox couples and found the results were consistent with the band edges shifting with the reversible potential of the redox couples. These shifts in the band edges with the potential of the redox couple imply that the flat band potential also shifts with the redox couple.…”
Section: Center For Coal and Minerals Processing April 1996mentioning
confidence: 68%